The effects of calcium and potassium on CO2 gasification of birch wood in a fluidized bed. (15th May 2017) - Kramb, Jason; Gómez-Barea, Alberto; DeMartini, Nikolai; Romar, Henrik; Doddapaneni, Tharaka Rama K.C.; Konttinen, Jukka
Highlights: Fluidized bed gasification of raw, leached, Ca doped and K doped wood. Effects of Ca and K on pyrolysis and char behavior. Char characterization using SEM-EDS, BET surface area and ICP-OES. Abstract: Birch wood was leached of its naturally occurring ash forming elements and doped with three concentrations of calcium or potassium before being gasified in a laboratory bubbling fluidized bed reactor. The wood samples were pelletized and inserted into a fluidized bed reactor where they were first pyrolyzed with N2 and then gasified with CO2 . In addition to tracking the gas concentration of the exit gas, char samples were taken from the fluidized bed and analyzed to study the char properties. The presence of potassium in the biomass was found to have a significant influence on the structure of the resulting char, however potassium did not have an observable catalytic effect on the overall gasification reaction rate with CO2 due to the formation of a unreactive coke layer on the char surface. In contrast, calcium did increase the char conversion rate and is likely the primary active catalyst in gasification of birch wood with CO2 .